Optimalisasi Pertumbuhan Bayi dengan Baby Massage and Spa - Asih, Yusari; Mirah WS, I Gusti Ayu (Politeknik Kesehatan Tanjung Karang, 2019)
Baby Massage and Spa was a traditional effort that uses a holistic approach through comprehensive care using a combination of massage and water therapy methods that are carried out in an integrated manner to balance the body, mind, and feelings. Age 3-6 months is the right time for babies to do massage and spa. The purpose of this study was to determine the effect of baby massage and spa on the growth of infants aged 3-5 months in Pringsewu District in 2018. This study uses a quasi-experimental approach with research design pre and post-test with control group design. The purposive sampling technique was taken with a sample of 30 infants as the intervention group and 30 infants as the control group. Data were processed using computerization and analyzed using the T-Test. The results showed that there were significant differences between body weight, body length and baby head circumference in the pre and post-treatment. There was no significant difference in the average increase in infant weight between babies who were carried out by baby massage and spa with babies who were not carried out by baby massage and spa with p-value 0.116. There is a significant difference in the baby's body length and head circumference performed by baby massage and spa with those not carried out by baby massage and spa with p-value 0.000. Baby Massage and Spa has a significant effect on increasing the growth of babies aged 3-5 months.